The Role of Inspiratory Muscle Training in Sickle Cell Anemia Related Pulmonary Damage due to Recurrent Acute Chest Syndrome Attacks - Burcu Camcıoğlu; Meral Boşnak-Güçlü; Müşerrefe Nur Karadallı; Şahika Zeynep Akı; Gülsan Türköz-Sucak (Case Reports in Hematology)
Background. The sickling of red blood cells causes a constellation of musculoskeletal, cardiovascular, and pulmonary manifestations. A 32-year-old gentleman with sickle cell anemia (SCA) had been suffering from recurrent acute chest syndrome (ACS). Aim. To examine the effects of inspiratory muscle training (IMT) on pulmonary functions, respiratory and peripheral muscle strength, functional exercise capacity, and quality of life in this patient with SCA. Methods. Functional exercise capacity was evaluated using six-minute walk test, respiratory muscle strength using mouth pressure device, hand grip strength using hand-held dynamometer, pain using Visual Analogue Scale, fatigue using Fatigue Severity Scale, dyspnea using Modified Medical Research Council Scale, and health related quality of life using European Organization for Research and Treatment of Cancer QOL measurement. Results. A significant improvement has been demonstrated in respiratory muscle strength, functional exercise capacity, pain, fatigue, dyspnea, and quality of life. There was no admission to emergency department due to acute chest syndrome in the following 12 months after commencing regular erythrocytapheresis. Conclusion. This is the first report demonstrating the beneficial effects of inspiratory muscle training on functional exercise capacity, respiratory muscle strength, pain, fatigue, dyspnea, and quality of life in a patient with recurrent ACS.